Apply to Row 2 : Row 2 + Row 1
2x + 2y + 3z = 0
y + 4z = -3
2x + 3y + 3z = 5
Apply to Row 3: Row 3 - Row 1
2x + 2y + 3z = 0
y + 4z = -3
y = 5
Apply to Row 3: Row 3 - Row 2
2x + 2y + 3z = 0
y + 4z = -3
-4z = 8
Simplify rows
2x + 2y + 3z = 0
y + 4z = -3
z = -2
Note that the matrix is in echelon form now. The next steps are for back substitution.
Apply to Row 2: Row 2 - 4 Row 3
2x + 2y + 3z = 0
y = 5
z = -2
Apply to Row 1: Row 1 - 3 Row 3
2x + 2y = 6
y = 5
z = -2
Apply to Row 1: Row 1 - 2 Row 2
2x = -4
y = 5
z = 2
Simplify the rows
x = -2
y = 5
z = -2